Sequencing of blaIMP-Carrying IncN2 Plasmids, and Comparative Genomics of IncN2 Plasmids Harboring Class 1 Integrons - Jiang, Xiaoyuan; Yin, Zhe; Yin, Xiuyun; Fang, Haihong; Sun, Qiang; Tong, Yigang; Xu, Yuanhong; Zhang, Defu; Feng, Jiao; Chen, Weijun; Song, Yajun; Wang, Jinglin; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
This work presents the complete nucleotide sequences of p0801-IMP from Klebsiella pneumoniae, p7121-IMP from K. oxytoca, and p17285-IMP from Citrobacter freundii, which are recovered from three different cases of nosocomial infection. These three plasmids represent the first fully sequenced blaIMP-carrying IncN2 plasmids. Further comparative genomics analysis of all the five integron-carrying IncN2 plasmids p0801-IMP, p7121-IMP, p17285-IMP, pJIE137, and p34983-59.134k indicates that they possess conserved IncN2 backbones with limited genetic variations with respect to gene content and organization. Four class 1 integrons (blaIMP-1-carrying In1223 in p0801-IMP/p7121-IMP, blaIMP-8-carrying In655 in p17285-IMP, In27 in pJIE137, and In1130 in p34983-59.134kb), two insertion sequence-based transposition units (ISEcp1-orfRA1-14 in p17285-IMP, and ISEcp1-blaCTX-M-62-Δorf477-orfRA1-14 in pJIE137), and a novel Tn1696-related transposon Tn6325 carrying In1130 in p34983-59.134kb are indentified in the plasmid accessory regions. In1223 and In655 represent ancestral Tn402-associated integrons, while In27 and In1130 belong to complex class 1 integrons. The relatively small IncN2 backbones are able to integrate different mobile elements which carry various resistance markers, promoting the accumulation and spread of antimicrobial resistance genes among enterobacterial species.